Tanya Luna and Alex Mendizabel. - Sahl, Ted (photographer):::Creator::::::::::::
Tanya Luna and Alex Mendizabel in formal dress and wearing crowns. Tanya holds a scepter and Alex wears a sash. Trophies for each are on the floor by their feet.